2006
DOI: 10.1093/ageing/afl067
|View full text |Cite
|
Sign up to set email alerts
|

Their last 6 months: suffering and survival of end-stage dementia patients

Abstract: Objective: to study possible interrelations existing between the Mini-Suffering State Examination (MSSE) scale and survival of end-stage dementia patients. Methods: a cohort study of 252 end-stage dementia patients with a 6-month follow-up period, conducted in a Division of Geriatric Medicine of a general hospital. We included 134 consecutive bedridden end-stage dementia patients admitted during a 36-month period, and surviving in the ward for <6 months. Interrelations between survival and admission MSSE score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 25 publications
(28 reference statements)
1
78
0
3
Order By: Relevance
“…Tube feeding varied between 4% and 39% in several US studies [39,45,47,63,66], and was 73% in Israel [67]. Hospitalization shortly before death was frequent in multi-site studies in US nursing homes [45,47,66].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Tube feeding varied between 4% and 39% in several US studies [39,45,47,63,66], and was 73% in Israel [67]. Hospitalization shortly before death was frequent in multi-site studies in US nursing homes [45,47,66].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
“…The results of selected studies have been integrated in a recent review, showing considerable unmet needs in families [85]. Through the beginning of 2010 (Box 1, Table 1), at least 45 studies [28,[33][34][35][36][37][38][40][41][42][43]46,47,52,60,61,63,65,66,80,[86][87][88][89][90][91][92][93][94][95][96][97][98][99]110] in another 26 publications [39,44,45,53,54,64,67,69,[111][112][113][114][115]…”
Section: Research Trends In Dementia At the End Of Lifementioning
confidence: 99%
“…It was also found that the suffering level of end-stage dementia (ESD) patients [18,19] and the struggle of family members [20] escalated during the dying process, until demise. Established correlations could hypothetically be explained by the enhanced level of the patients' body entropy.…”
Section: Discussionmentioning
confidence: 99%
“…Life expectancy is more emphatically curtailed by dementia than it is by other psychiatric syndromes (Jolley & Baxter, 1997). Yet the evidence for suboptimal care persists, especially in the terminal phase (Wilden & Wright, 2002), with studies in the USA and Israel confirming the somewhat dismal picture (Mitchell et al, 2004;Aminoff & Adunsky, 2006).…”
Section: Is There a Need For Improved Palliative Care In Dementia?mentioning
confidence: 99%